7.18 IMPORTANCE OF MEDICINAL PLANTS IN MEDICINE - Kuriyazova Saodat Matkarimovna., Olimova Munira Utkirjon qizi (Innovative technologies in construction Scientific Journal, 2024)
Nowadays, medicinal plants are of great importance in medicine, and people interested in them are increasing day by day. Modern scientific medicine has a number of new drugs and treatment methods, but in some cases, the types of drugs used are chemical products, and they are processed differently. They, in turn, serve as a means of causing various side effects, that is, additional diseases. In such a situation, in many cases, both scientific medical workers and the population themselves are paying more attention to natural products and medicinal plants than to the use of drugs. The absolute harmlessness and usefulness of medicinal plants and natural medicines obtained from them is the reason for the sharp increase in scientific research in medicine. АННОТАЦИЯ. В настоящее время лекарственные растения имеют большое значение в медицине, и интересующихся ими людей с каждым днем становится все больше. Современная научная медицина располагает рядом новых лекарств и методов лечения, но в некоторых случаях используемые препараты представляют собой химические продукты и обрабатываются по-разному. Они, в свою очередь, служат средством, вызывающим различные побочные эффекты, то есть дополнительные заболевания. В такой ситуации во многих случаях как научные медицинские работники, так и само население уделяют больше внимания натуральным продуктам и лекарственным растениям, чем применению лекарств. Абсолютная безвредность и полезность лекарственных растений и получаемых из них натуральных лекарств является причиной резкого увеличения научных исследований в медицине. ANNOTATSIYA. Hozirgi kunda dorivor o’simliklarni tibbiyotdagi ahamiyati katta bo’lib, ularga qiziquvchilar kundan-kunga ortib bormoqda. Zamonaviy ilmiy tibbiyotda bir qancha yangi dori vositalari va davolash usullari mavjud, ammo ayrim hollarda foydalanilayotgan dori turlari kimyoviy mahsulotlar bo’lib, ularga turlicha ishlov beriladi. Ular o’z navbatida turli xil nojo’ya asoratlarga, ya’ni qo’shimcha kasalliklarni chaqiruvchi vosita bo’lib xizmat qiladi. Bunday vaziyatda ko’p hollarda ilmiy tabobat xodimlari ham, aholining o’zi ham dori vositalardan foydalanishdan ko’ra ko’proq tabiiy mahsulotlar, dorivor o’simliklarga e’toborni kuchaytirib bormoqdalar. Dorivor o’simliklar va ulardan olinadigan tabiiy dori vositalarni mutlaq zararsizligi va foydasi, tibbiyotda ilmiy tadqiqotlarni keskin ortishiga sabab bo’lmoqda. KEY WORDS: sabur, stimulants, extract fungicide, dermatosis, psoriasis, phytotherapy, resin, essential oil, carotenoids, and flavonoids. Medicinal plants are plants and herbs used in the treatment of humans and animals, prevention of diseases, as well as in the perfumery and cosmetics industry. There are more than 4,500 tall plants in Uzbekistan, and more than 700 of them are medicinal plants. Today, the interest in medicinal plants is increasing, and people with aging and chronic diseases prefer natural means to activate the immune system. Currently, about 40-47% of the drugs used in medicine are obtained from plant raw materials. Dried trunk, shoot, root, nodule, rhizome, bulb, flower, leaf, fruit of medicinal plants are used as medicine.